Biosynthesis and characterization of gold and silver nanoparticles by pink guava (psidium guajava) waste extract / Norashikin Ahmad Zamanhuri, Mohamed Syazwan Osman and Rasyidah Alrozi - Osman, Mohamed Syazwan; Alrozi, Rasyidah (Research Management Institute (RMI), 2012)
There is an increasing commercial demand for nanoparticles due to their wide applicability in various areas such as electronics, catalysis, chemistry, energy and medicine. Metallic nanoparticles are traditionally synthesized by wet chemical techniques, where the chemicals used are quite often toxic and give impact to the human health and environment. Metal nanostructures have unusual physicochemical properties and biological activities compared to their bulk parent materials. In this study, silver and gold nanoparticles (AgNPs and AuNPs) were synthesized from aqueous silver nitrate and auric acid solution respectively, through a simple and eco-friendly route using pink guava waste extract (PGWE) as reductant and stabilizer. The resulting silver and gold nanoparticles were characterized by using Ultraviolet-visible (UV-vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and transmission electron microscopy (TEM). AgNPs and AuNPs vary in size according to different amount of PGWE and silver nitrate and auric acid concentration used for the synthesis. Formation of AgNPs and AuNPs was confirmed by the color changed and by surface Plasmon spectra by using Uv-Vis spectrometer as well as absorbance peaks lie between 400 to 500 nm. The silver and gold nanoparticles obtained using this source have particles size in the range of 0- 50 nm. It was found that the increase in silver nitrate and uric acid concentration leads to the increasing size of AgNPs and AuNPs produced.